Comparison of two data acquisition and processing systems of Moller polarimeter in Hall A of Jefferson Lab - Vereshchaka, V.V.; Glamazdin, O.V.; Pomatsalyuk, R.I. (Вопросы атомной науки и техники, 2014)
Two data acquisition and processing systems are used simultaneously to measure electron beam polarization by Moller polarimeter in Hall A of Jefferson Lab (Newport News, VA, USA). The old system (since 1997) is fully functional, but is not repairable in case of malfunction (system modules are not manufactured anymore). The new system (since 2010) based on flash-ADC is more accurate, but currently requires more detailed adjustment and further improvement. Description and specifications of two data acquisition and processing systems have been given. The results of polarization measurements during experiments conducted in Hall A from 2010 to 2012 are compared.